Pengaruh Dewan Komisaris Independen, Komite Audit, Leverage dan Intensitas Modal Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017 - Marwan Faiz Hilmi; Sisti Nadia Amalia; Zul Amry; Susi Setiawati (Owner : Riset dan Jurnal Akuntansi, 2022)
The problem in this study is how the influence of the Independent Board of Commissioners, Audit Committee, Leverage and Capital Intensity on manufacturing companies listed on the Indonesia Stock Exchange in the year. The purpose of this study was to examine the influence of the Independent Board of Commissioners, Audit Committee, Leverage and Capital Intensity on manufacturing companies listed on the Indonesia Stock Exchange. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange. The sampling method used purposive sampling and obtained a sample of 116 companies. The analysis technique used is simple linear regression analysis with the help of SPSS. The proxy used to measure Tax Avoidance uses the Tax Expense divided by Pre-Tax Profit. The proxy used to measure the Independent Board of Commissioners using Independent Commissioners is divided by the total number of members. The proxy used to measure the Audit Committee uses Dummy which is worth 1 if the audit committee is> 3, and is worth 0 if the audit committee <3. The proxy used to measure leverage uses Total Debt divided by Total Assets. For the proxies used to measure Capital Intensity using Total Net Fixed Assets divided by Total Assets. The results of hypothesis testing obtained with a significant level of 5% indicate that only the audit committee has an influence with a significance value of 0.029 <0.05 against tax avoidance. While the results of hypothesis testing for independent board of commissioners, leverage and capital intensity have no effect on tax avoidance.